A feasibility study of gemcitabine, S-1 and leucovorin combination therapy (GSL) for advanced biliary tract cancer. (4th July 2019) - Takahara, Naminatsu; Isayama, Hiroyuki; Nakai, Yousuke; Sasaki, Takashi; Saito, Kei; Sato, Tatsuya; Hakuta, Ryunosuke; Ishigaki, Kazunaga; Saito, Tomotaka; Hamada, Tsuyoshi; Mizuno, Suguru; Kogure, Hirofumi; et al.
Abstract : Objective : Gemcitabine and cisplatin (GC) combination chemotherapy is the current standard of care for patients with advanced biliary tract cancer (BTC). Recently, a randomized controlled trial showed the non-inferiority in overall survival of gemcitabine and S-1 (GS) compared to GC. Because leucovorin is known to enhance the activity of S-1, we conducted this study to evaluate the feasibility of combination therapy of gemcitabine, S-1 and leucovorin (GSL).Methods : Advanced BTC patients without prior treatment other than surgery or adjuvant chemotherapy were eligible to this study. Gemcitabine was administered at a dose of 1000 mg/m 2 on day 1, and oral S-1 at a dose of 40 mg/m 2 and oral leucovorin at a dose of 25 mg twice daily on days 1–7, every 2 weeks. The primary endpoint was PFS and the secondary endpoints included OS, objective tumour response and the safety.Results : Between June 2013 and December 2015, 20 patients with advanced BTC (12 gallbladder, 4 extrahepatic, 2 intrahepatic, 2 ampulla) including 16 unresectable disease and 4 recurrent disease were enroled. The median PFS and OS were 5.5 (95% confidence interval [CI], 1.8 – not reached) and 16.0 (95% CI, 6.4–20.8) months, respectively. A partial response was achieved in 3 (15%) and stable disease in 8 (40%), giving a disease control rate of 55%. Major grade 3/4 toxicities included neutropenia (30%), anaemia (5%), stomatitis (15%), diarrhoea (15%) and anorexia (10%). There were no treatment-related deaths.Conclusions : This study showed the feasibility and potential efficacy of GSL as a first-line treatment in patients with advanced BTC.